2017
DOI: 10.17219/acem/63140
|View full text |Cite
|
Sign up to set email alerts
|

The effect of crystalloid infusion on body water content and intra-abdominal pressure in patients undergoing orthopedic surgery under spinal anesthesia

Abstract: Background. Crystalloids are frequently used for the correction of spinal anesthesia-induced hypotension, intraoperative bleeding, or vaporisation from surgical wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…However, patients who received RL serum experienced more adverse effects in comparison with other groups. In this regard, the results of a similar study are in line with the results of the current study (10) indicating the least changes among those who received RL serum. It seems that the modified ingredients of RL serum are the main reason for the minimum changes and adverse effects.…”
Section: Discussionsupporting
confidence: 90%
“…However, patients who received RL serum experienced more adverse effects in comparison with other groups. In this regard, the results of a similar study are in line with the results of the current study (10) indicating the least changes among those who received RL serum. It seems that the modified ingredients of RL serum are the main reason for the minimum changes and adverse effects.…”
Section: Discussionsupporting
confidence: 90%
“…There is a significant positive correlation between increased IAP with a positive fluid balance and decreased IAP with a negative fluid balance [97]. A liberal fluid strategy, compared to a restrictive fluid strategy, is associated with a significantly higher rise in IAP after surgery [94]. Furthermore, there was a strong correlation between IAP and extracellular water content in the liberal subgroup, which is in keeping with the hypothesis of fluid extravasation being one of the critical mechanisms in the development of IAH.…”
Section: Resuscitation Fluid and Risk Factorssupporting
confidence: 77%
“…Six prospective studies (460 surgical patients) [92][93][94][95][96][97], four retrospective studies (189 patients) [88,89,98,99] and seven case reports (see Table 3) in adults [63,90,91,[100][101][102][103], describe the association between fluid and ACS (Supplementary Table S4.) Incidence Dalfino et al, showed how a positive fluid balance comprised one of three independent predictors for developing IAH (31.8%), together with baseline IAP and central venous pressure [104].…”
Section: Surgical Patientsmentioning
confidence: 99%
“…We defined the LF rate as four times the CF rate because there is a lack of consensus on what a "liberal" fluid strategy means in clinical practice (Rahbari et al, 2009). Nevertheless, the difference between the CF and LF infusion rates was close to that in many other studies (Holte et al, 2007;Kotlińska-Hasiec et al, 2017;Lobo et al, 2011;Shin et al, 2018). Even though CO LV and MAP were similar between the groups and time points, the fluid rate difference was sufficient to create two different hemodynamic profiles as demonstrated by lower SVV LV and VCCI at T 60 in the LF-PCV group.…”
Section: Discussionmentioning
confidence: 94%
“…The histologic features better represent mild lung injury from LPS instillations in small animals (Matute-Bello et al, 2011). Second, the LF rates used here were relatively high; nevertheless, studies show similar fluid rates in clinical scenarios (Holte et al, 2007;Kotlińska-Hasiec et al, 2017;Lobo et al, 2011;Shin et al, 2018). Furthermore, we aimed to investigate groups with extreme and different fluid strategies.…”
Section: Limitationsmentioning
confidence: 98%